Influence of Price And Location on Belikopi Ploso Consumer Purchasing Decisions - Syaidah, Ainun; Munawaroh, Munawaroh; Susilowati, Lina (Journal of Business Management and Economic Development, 2023)
The aim of this study is to figure out how location and pricing affect consumer buying decisions in Belikopi Ploso. This study uses a quantitative methodology that uses a variety of linear regression analytic techniques. The population of the study consisted of all Belikopi Ploso clients. the Lemeshow formula-based sample of 100 people. The information was gathered using a questionnaire using a Linkert scale. The research data passed the tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. A significance value of t of 0.00 0.05 and the study's findings showed that 1) pricing significantly influenced Belikopi Ploso consumers' buying decisions, 2) The location has had a considerable impact on Belikopi Ploso consumers' purchase decisions, according to the t significance value of 0.044 0.050. 3) The F significance value of 0.00 0.05 showed that price and location both significantly affecedt the purchasing decisions of Belikopi Ploso consumers.